PENGARUH EARNINGS SURPRISE BENCHMARK TERHADAP PREDIKTABILITAS LABA DAN RETURN SAHAM - Vestari, Mekani (PRESTASI, 2012)
The aim of this research is to get an empirical evidence about the impact of earnings surprise benchmark on earnings predictability and stock return predictability. The population of this research is 163 manufacture firms which is listed in Indonesia Stock Exchange refer to Indonesian Capital Market Directory that require data for year 2005 until 2010. Based on purposive sampling method the sample in this research is for about 123 firms. Market response is the dependent variable that measured with stock return for period t. Market response is influenced by independent variables which includes earnings predictability, stock returns predictability, earnings yield, asset turnover, operating cash to net income ratio, dividend pay out ratio and the association moderated with earnings surprise benchmark. Earnings predictability is measured by earnings (earnings per share) changeÂ for period t, t+1, and t+2. Return predictability is measured by stock return for period t+1, and t+2. Earnings surprise benchmark is a moderating variable which interacts with all independent variables. The dummy variable is one when the net income is in the range of mean to standard deviation as a proxy of high earnings quality and zero when the net income is out of the mean to standard deviation with assumption that management do windows dressing and taking a bath. Data analysis is using linear regression.The analysis result shows that earnings surprise benchmark does not have significant impact on stock return predictability but have significant impact on earnings predictability. It shows that investor give enough attention to earnings with high quality. Keyword : earnings surprise benchmark, earnings predictability, stock return predictability, earnings per share, stock return